China and India : better jaw-jaw than war-war - Zhang, Baohui (2020)
The deadly clash between China and India in the Galwan Valley, Ladakh, has heightened the probability of war along their border. In fact, they are trapped in the most dangerous great power relationship in the world. China and India must engage each other more, not less. To paraphrase Churchill: Better to “talk-talk”, than to “war-war”.